ANALISIS HUBUNGAN GAYA KEPEMIMPINAN DAN KOMPETENSI KOMUNIKASI DALAM ORGANISASI - Edah Jubaedah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Many studies tried to explore the correlation between leadership and communication competence and other organization variables. Some researchers focused on finding the association between leadership styles and communication competence, others focused on examining the influence of chose variables to employees job satisfaction and work performance. These studies proved that there is a relationship between the leader’s use of leadership styles and the leader’s communication competence. Its also showed that there is a strong relationship between supervisor communication competence and employee communication satisfaction.